Rheumatoid Factor Isotypes in a Sample of Iraqi Rheumatoid Arthritis Patients - Raghad Hassan Hussein (Journal of Global Pharma Technology, 2018)
Rheumatoid arthritis is a chronic inflammatory disease with an autoimmune origin. This disease primarily involves the small joints with subsequent systemic involvement. Rheumatoid factor is one of several biomarkers that characterize this disease. The prevalence of rheumatoid arthritis has increased in Iraq in recent decades. This study aimed to investigate the level of three RF isotypes in a sample of Rheumatoid arthritis patients. The study involved 100 Iraqi rheumatoid arthritis patients aged 5-72 years. The mean age for the patients included in the study was a 41.04 ±14.25 year with the majority of patients (42%) being in the age group 40-59 years. A highly significant difference in the prevalence of rheumatoid arthritis was found between female (82%) and male (18%) patients included in the study (p<0.01). Qualitative estimation of RF isotypes showed that the highest positivity was for RF-IgG (42%) followed by RF-IgA (29%) and RF-IgM (28%).Quantitative estimation of RF-isotypes showed that the mean value for serum IgA, IgG and IgM in patients included in this study was 41.04 U/ml, 39.6 U/ml and 48.6 U/ml respectively. An interrelation was found between RF-IgG and RF-IgM titers (r=0.54). The results of this study confirm the importance of measuring multiple RF isotypes in rheumatoid arthritis patients.Keywords: Rheumatoid arthritis, Rheumatoid factor isotypes, RF-IgM.